MO545: Estimated Proximal Tubule Fluid Phosphate Concentration: An Early Marker of CKD-MBD?. (3rd May 2022) - Rotondi, Silverio; Mazzaferro, Sandro; Pasquali, Marzia; Tartaglione, Lida; Tinti, Francesca; Perrotta, Adolfo
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) typically associates with mineral bone disorders (CKD-MBD), kidney damage progression and increased morbidity and mortality. CKD-MBD develops early in CKD and, if promptly detected, could receive therapeutic attention. However, early markers of CKD-MBD like fibroblast growth factor 23 (FGF23) and α-Klotho are not widely available in clinical practice. Recently, estimated proximal tubule fluid phosphate concentration (ePTFp) has been proposed as a novel early marker of MBD. In fact, in CKD patients, along with the progressive reduction of nephron number, FGF23 increments are necessary to reduce renal tubular phosphate reabsorption and to maintain phosphate balance. As a consequence, PTFp concentration per single nephron progressively increases, leading to renal tubular cells overload, interstitial inflammatory response and progression of kidney damage. For this reason, PTFp concentration could represent an early marker of CKD-MBD. OBJECTIVE: To evaluate the relationship between ePTFp and early markers of MBD in patients with CKD stage G2–4. METHOD: In CKD patients stage G2–4, we evaluated serum FGF23, α-Klotho, parathyroid hormone (PTH) and ePTFp [ePTFp = (phosphaturia/creatininuria) x creatininemia x 3, 33]; 30 healthy subjects (age 40 ± 5 years) were the control group for normal value of ePTFp. RESULTS: In 68 CKD patients (age 58.9 ± 15.6 years eGFR 45 ± 21 mL/min), ePTFp averaged 2.4 ± 1.3 mg/mg which was significantly higher than in the control group (ePTFp = 1.2 ± 0.5; P < 0.01). ePTFp increased progressively along with the increasing CKD stages (stage 2: 1.6 ± 0.6; stage 3: 2.3 ± 0.9; stage 4: ± 1.5; P < 0.001) with values significantly higher than the control group since CKD stage 2 (ePTFp: Control group = 1.2 ± 0.5 versus stage 2 = 1.6 ± 0.6; P < 0.05). ePTFp showed a positive correlation with FGF23 ( r : 0.69; P < 0.001) and PTH ( r :0.310; P < 0.05) and a negative correlation with α-Klotho ( r : −237; P < 0.05) and eGFR ( r : −647; P < 0.001). CONCLUSION: Our data showed early and progressive increments of ePTFp in CKD patients since CKD stage 2. These increments are paralleled by increased FGF23 and PTH and decreased α-Klotho, suggesting reciprocal pathophysiologic dependence. Accordingly, ePTFp could represent a surrogate of renal tubular cells phosphate overload, indicative of CKD-MBD development. ePTFp can be easily obtained in everyday clinical routine and could represent a reference to make therapeutic choices (e.g. dietary phosphate control). In conclusion, ePTFp could identify patients at risk of developing the CKD-MBD maladaptive response with increased risk of kidney damage progression.